Seed Priming: A Potential Supplement in Integrated Resource Management Under Fragile Intensive Ecosystems - Devika, O. Siva; Singh, Sonam; Sarkar, Deepranjan; Barnwal, Prabhakar; Suman, Jarupula; Rakshit, Amitava (Frontiers in Sustainable Food Systems, 2021)
A majority of agricultural activities are conducted under fragile lands or set-up. The growth and development of crops are negatively affected due to several biotic and abiotic stresses. In the current situation, research efforts have been diverted toward the short-term approaches that can improve crop performance under changing environments. Seed treatment or priming technology is in a transition phase of its popularity among resource-poor farmers. Suitable policy intervention can boost low-cost techniques to implement them on a larger scale in developing countries and to harness the maximum benefits of sustainable food production systems. Primed seeds have high vigor and germination rate that help in seedling growth and successful crop stand establishment under stress conditions. This review is attempted to assess different seed priming techniques in terms of resource use efficiency, crop productivity, cost–benefit balance, and environmental impacts. Moreover, a comprehensive study of the mechanisms (physiological and biochemical) of seed priming is also elaborated. A detailed examination of the applications of priming technology under diverse agroecosystems can improve our understanding of the adaptive management of natural resources.